PENGANGKAT BARANG PADA KONDISI BANJIR BERBASIS RASPBERRY PI MELALUI TWITTER SEBAGAI OUTPUT MEDIA INFORMASI - Ferry Sudarto; Eka Purwandari; Aldien Sora Andrea (UNIVERSITAS RAHARJA, 2015)
Appointment of goods is essential in the operation of the company. Currently forklift with manual or automatic that has not been working efficiently. Especially forklift in flood conditions. So we need tools that work the forklift automatically on flood conditions, the process of appointment, and notify the results of such appointments by personal message via the output of media-based Raspberry Pi Twitter. The circuit uses a forklift Soil Moisture Sensor is used to detect water in the vicinity of the sensor. Raspberry Pi will process the input and give orders to the Motor Servo work to move the hinge table so the table is automatically lifted. Lifting these goods become important in minimizing damage toproperties affected by flooding. So as to improve the efficiency of lifting equipment goods in flood conditions. If the Soil Moisture Sensor exposed to water it will automatically give the data to the Raspberry Pi and processed into information. Once processed, the Raspberry Pi will give two orders to Twitter as output information and the Servo Motor as the physical output will move. The process that is done it does not take long, after the sensor is exposed to water, the appliance works with a period of about 1-2 minutes. Then the items on the table would be safe to avoid flooding with automatic.